Developing and Assessing Intercoder Reliability in Studies of Group Interaction - Compton, D'Lane; Love, Tony P.; Sell, Jane (Sociological methodology, 2012)
Although group interaction is a rich source of data, it offers many challenges for analysis. We discuss how pretesting can solve many coding and reliability issues before the actual data collection and analysis. We also consider how coding schemes can be developed, how coders can be trained, and how coder reliability can be ascertained. We examine the properties of different estimates of intercoder reliability and detail how these relate to decisions about the data.